Comparison and recent progress of molecular imprinting technology and dummy template molecular imprinting technology. Issue 39 (27th September 2021) - Chen, Ru-Nan; Kang, Shu-He; Li, Jia; Lu, Li-Na; Luo, Xing-Ping; Wu, Lan
Abstract : Molecular imprinting technology for the preparation of polymers with specific molecular recognition function had become one of the current research hotspots. Abstract : Molecular imprinting technology for the preparation of polymers with specific molecular recognition function had become one of the current research hotspots. It has been widely applied in chromatographic separation, antibody and receptor mimetics, solid-phase extraction, bio-sensors, and other fields in the last decades. In this study, molecular imprinting technology was summarized from the points of templates and dummy templates, and four typical target analytes were selected to compare the differences between templates and dummy templates. The current status and prospects of molecular imprinting technology were also proposed.